Factors influencing quantity surveying services performance in Nigeria / Esther Ilori Ebunoluwa and Grace Kehinde Ojo. - Ebunoluwa, Esther Ilori; Ojo, Grace Kehinde (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Quantity surveying profession is faced with great challenges concerning recognition and survival in Nigeria. Usually, this could be overcome by being proactive in dealing with factors that could influence their services performance. Quiet numbers of factors are affecting the performance of quantity surveying firms in Nigeria; which makes their survival to be a matter of concern to the researchers. Therefore, this paper evaluated the extent to which the performance of quantity surveying firms is being influenced by internal and environmental factors with a view to increasing the recognition and survival of the firm in the competitive business environment. Employee quantity surveyors assessed internal factors while employers of quantity surveying firms assessed external factors. One hundred and thirty-one (131) respondents comprising eighty-five (85) employees and forty-six (46) employers of registered quantity surveying firms were sampled randomly. Data were collected through administration of questionnaire on influencing factors; the collected data were subjected to mean analysis and analysis of variance (ANOVA). The findings showed that lack of recognition of the employees by the management influenced the performance of employees mostly; the employees agreed on the influence of this factor on the overall performance of firm. On external factors, findings revealed that technological changes and tough competition have high level of influence on the performance of quantity surveying firms in the built environment. In addition, the employers have similar view on the influence of these factors @ p>0.05. The study concluded that lack of recognizing the employees by the firm, technological changes and tough competition influenced the performance of quantity surveying services in Nigeria; these factors had affected the recognition of quantity surveying profession in the competitive environment. Therefore, the factors should be given adequate and prompt consideration so as to minimize their adverse effects on the survival of Quantity Surveying Firms in Nigeria.